Algorithm of Behaviour of Virtual Avatars During Public Speaking Training in a VR Environment - Karol Jędrasiak; Robert Robert Wolański; Damian Bereska (Safety & Fire Technology)
Aim: This article aims to explore and advance the field of public speaking training through the use of virtual reality (VR) and virtual avatars. The focus is on addressing the challenges faced in traditional public speaking training methods by leveraging the capabilities of VR technology. Project and methods: The project involved developing an innovative algorithm designed to control the behaviour of virtual avatars during public speaking training in a VR environment. This algorithm integrates multiple aspects of human communication, including posture modelling, voice modulation, greet- ings mannerisms, eye contact management, gestural communication and interactive responsiveness. The methodology combined theoretical research and practical implementation, involving a comprehensive review of existing solutions and the development of a sophisticated, integrated algorithm. The project utilised advanced programming techniques and the latest VR technology, tested in simulated public speaking scenarios. Results: The results of implementing this algorithm in VR-based training applications showed a significant improvement in the authenticity and effec - tiveness of public speaking training. The virtual avatars, powered by the algorithm, were able to simulate realistic human behaviours and responses, thus providing a more engaging and immersive learning experience for users. The application offered a variety of realistic training scenarios, interactive avatar feedback, customisation options, and progress tracking and analysis features. The study found that the algorithm successfully enhanced participants' public speaking skills, reducing anxiety and improving their overall communication abilities. Conclusions: The research conducted in an “e-Zawody” project concludes that the integration of VR and virtual avatars significantly enhances public speaking training, offering a novel, effective and engaging approach. The development of the algorithm marks a pivotal advancement in educational technology, providing a platform that surpasses traditional training methods. However, the study acknowledges technological limitations and the need for ongoing research and development. Future efforts should focus on enhancing the realism and interactivity of virtual avatars and expanding the applica- tion of VR-based training across various fields. The findings suggest a promising direction for the future of public speaking training, with VR technology poised to play a crucial role in the evolution of educational methodologies. Keywords: public speaking training, virtual reality, opportunity to practise, behaviour synthesis, virtual avatars